Xavier Bougarel, Hannes Grandits and Marija Vulesica, eds., Local Dimensions of the Second World War in Southeastern Europe - Tzoukas, Vangelis (Historein, 2021)
Review of Xavier Bougarel, Hannes Grandits and Marija Vulesica, eds. Local Dimensions of the Second World War in Southeastern Europe. Oxford: Routledge, 2019. 281 pp.